2020
DOI: 10.37531/sejaman.v3i2.568
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Leverage, Profitabilitas Dan Kepemilikan Manajerial Terhadap Manajemen Laba

Abstract: Penelitian ini dilakukan untuk mengetahui pengaruh dari Leverage, Profitabilitas, dan Kepemilikan Manajerial terhadap Manajemen Laba dengan menggunakan ukuran dan umur perusahaan sebagai variabel kontrol. Populasi dalam penelitian ini adalah perusahaan tambang yang terdaftar di Bursa Efek Indonesia (BEI) periode 2016-2018. Jumlah perusahaan pada penelitian ini sebanyak 23 dengan menggunakan teknik puposive sampling. Penelitian ini menggunakan analisis regresi data panel, dengan beberapa pemilihan model uji cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 8 publications
4
7
0
11
Order By: Relevance
“…The ability of embedded funds to generate income in the form of assets or capital invested in rotating firms. This study is in line with Febria [22]'s study which found that the activity ratio does not affect earnings management.…”
Section: Effect Of Activity Ratio (Total Asset Turn Over) On Earnings...supporting
confidence: 92%
See 1 more Smart Citation
“…The ability of embedded funds to generate income in the form of assets or capital invested in rotating firms. This study is in line with Febria [22]'s study which found that the activity ratio does not affect earnings management.…”
Section: Effect Of Activity Ratio (Total Asset Turn Over) On Earnings...supporting
confidence: 92%
“…This has a negative influence on income, which is decreasing, and investors are becoming less interested in investing. The same results are shown in the study of Widianingrum and Sunarto [21], and Febria [22] that leverage does not affect earnings management.…”
Section: Effect Of Leverage (Debt To Asset Ratio) On Earnings Managementsupporting
confidence: 83%
“…The results of research by (Ahmad & etc, 2012) found that professional commitment determines not only professional loyalty to the profession, but also compliance with professional code of ethics. (Halim, 2013) also found that a strong auditor's commitment to his/her profession means that the auditor upholds the rules and norms in the form of professional standards of public accountants and the code of ethics of the public accounting profession in carrying out his/her audit duties.…”
Section: Resultsmentioning
confidence: 99%
“…The research of auditor's professional commitment seems inexhaustible to be the object of research. But most of the research about professional commitment are analyzed based on the positivistic, for example: (Ahmad & etc, 2012), (Aranya & Ferris 1984), (Azis, 2016), (Gendron & etc, 2006), (Greenfield & etc, 2008), (Halim, 2013), (Hall & Smith, 2005), (Larkin, 1990), (Lord & DeZoort, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Modify information with accounting methods to deceive stakeholders based on the desired goals. The income statement becomes a benchmark for evaluating the company's performance and is used for economic decision-making (Febria, 2020;Hasty & Herawaty, 2017& Perdana, 2019. Earnings information can be the target of efforts to modify earnings as an opportunistic management action to maximize satisfaction (Hasty & Herawaty, 2017).…”
Section: Introductionmentioning
confidence: 99%